2021
DOI: 10.1177/2167702621998315
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Interfering With Intrusive but Not Voluntary Memories of a Trauma Film: Accounting for the Role of Associative Memory

Abstract: Intrusive memories of a traumatic event can be reduced by a subsequent interference procedure, seemingly sparing voluntary memory for that event. This selective-interference effect has potential therapeutic benefits (e.g., for emotional disorders) and legal importance (e.g., for witness testimony). However, the measurements of intrusive memory and voluntary memory typically differ in the role of associations between a cue and the emotional memory “hotspots.” To test this, we asked participants to watch a traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…As we noted earlier, we have in previous work demonstrated that the imagery-competing task intervention is successful in reducing intrusion rates while leaving factual and/or episodic components of the memory intact for voluntary retrieval (Lau-Zhu et al, 2019, 2021), consistent with dual representation accounts of intrusive memories (Brewin et al, 2010). This, however, leaves open the question of what precise features of the memories are being diminished (e.g., sensory–perceptual features), when they are transformed into a nonintrusive state, and how this relates to theoretical accounts on the basis of memory intrusions (e.g., Bisby et al, 2020; Brewin et al, 2010; Cohen & Kahana, 2022; Ehlers & Clark, 2000).…”
Section: Two Seals About Measuring Intrusionssupporting
confidence: 79%
See 1 more Smart Citation
“…As we noted earlier, we have in previous work demonstrated that the imagery-competing task intervention is successful in reducing intrusion rates while leaving factual and/or episodic components of the memory intact for voluntary retrieval (Lau-Zhu et al, 2019, 2021), consistent with dual representation accounts of intrusive memories (Brewin et al, 2010). This, however, leaves open the question of what precise features of the memories are being diminished (e.g., sensory–perceptual features), when they are transformed into a nonintrusive state, and how this relates to theoretical accounts on the basis of memory intrusions (e.g., Bisby et al, 2020; Brewin et al, 2010; Cohen & Kahana, 2022; Ehlers & Clark, 2000).…”
Section: Two Seals About Measuring Intrusionssupporting
confidence: 79%
“…Anderson & Green, 2001, as discussed in Schacter, in press). Indeed, we have demonstrated that the imagery-competing task intervention is successful in reducing intrusion rates while keeping voluntary retrieval of the memories themselves intact (Lau-Zhu et al, 2019, 2021). This point is critical because it is important that individuals are still able to deliberately retrieve details of a traumatic event when they choose to (e.g., to report or provide testimony in legal settings) but do not suffer from unwanted recollection at times when they do not want to (i.e., intrusive memory persistence).…”
Section: A Memory-based Intervention For Intrusive Memoriesmentioning
confidence: 98%
“…The findings also raise a number of questions, such as whether the observed day-dependent effects of hydrocortisone are specific to sensory-perceptual involuntary memories. In particular, would voluntary memory show a similar day-dependent effect (in the absence of a main effect of drug) if it was assessed repeatedly and matched to involuntary memory on various dimensions at test [ 63 ]? The current study also supports the notion that estradiol and progesterone are important determinants of memory functioning relevant to PTSD and other psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in both studies, recognition memory for the material was unaffected by the Tetris manipulation, suggesting that the intervention specifically impacted the emotional quality of those memories. Follow-up research moreover showed that whereas intrusive memories were downregulated by the Tetris intervention, voluntary memories were still intact (Lau-Zhu et al, 2021).…”
Section: Closing the Loop: From Stimulus To Response (And Back)mentioning
confidence: 99%